Leksikografovi zapiski o korpusnem slovarju - Čermák, František (Jezik in slovstvo, 2009)
In the following notes there will be an attempt made to emphasize some of the difficult problems and issues encountered during the compilation process of a monolingual dictionary. Since it is neither possible to be exhaustive nor detailed enough, the notes, preceded by some preliminary remarks (1), are split into two main sections (I and II). In Part I (2-4), an analysis of corpus data (drawing on the Czech language), exemplified and commented, is offered resulting at a lexical profile of a word, while in Part II (5-8) drawing on the previous part, a commented list of some of the main aspects and principles of the dictionary-making business will be presented. References to most of the points raised are to be found in the literature at the end.
Keywords: češčina; slovaropisje; Corpus linguistics; korpusno jezikoslovje; metodologija; slovarji